Cloning and nucleotide sequence of the gene for dihydrolipoamide acetyltransferase from Saccharomyces cerevisiae. - Niu, X D (1988)
A 537-base cDNA encoding a portion of Saccharomyces cerevisiae dihydrolipoamide acetyltransferase (acetyl-CoA:dihydrolipoamide S-acetyltransferase, EC 2.3.1.12) was isolated from a lambda gt11 yeast cDNA library by immunoscreening. This cDNA was subcloned and used as a probe to screen a lambda gt11 yeast genomic DNA library. Two overlapping clones were used to determine the complete sequence of the acetyltransferase gene. The composite sequence has an open reading frame of 1446 nucleotides encoding a presequence of 28 amino acids and a mature protein of 454 amino acids (Mr = 48,546). The deduced amino acid sequence contains the experimentally determined amino acid sequences of the amino terminus and two internal peptide fragments of the acetyltransferase. Hybridization analysis of yeast genomic DNA showed that the gene has a single copy. A 915-base segment of the acetyltransferase gene hybridized to a yeast mRNA of approximately equal to 1.6 kilobases. Analysis of the deduced amino acid sequence of the dihydrolipoamide acetyltransferase revealed a multidomain structure similar to those reported for the corresponding acetyltransferases from Escherichia coli and rat liver, and extensive sequence similarity among the three enzymes. However, the yeast enzyme contains only one lipoyl domain, in contrast to three lipoyl domains reported for the E. coli enzyme and apparently two for the rat liver enzyme.